Entrepreneurial Self-Employment and Work Engagement in MSMEs Through Autonomy and Rewards - Wuisan, Dewi; Manurung, John William; Wantah, Christoffel; Yuliana, Merryl Esther (Pandawan, 2025)
The rise of self-employment highlights the need to understand its implications on workers engagement, especially for those in Economically Dependent Solo Self-Employment (EDSSE) and Necessity Self-Employment (NSE). This study aims to examine the effects of these two self-employment types on skill discretion, rewards, autonomy, and work engagement, as well as the mediating roles of these three intrinsic job resources. Using a quantitative approach, data were collected via questionnaires from self-employed individuals in Jakarta who have worked for at least one year. Partial Least Square (PLS) analysis was employed to evaluate the relationships between variables. The results reveal that both EDSSE and NSE positively influence skill discretion, rewards, autonomy, and work engagement. Furthermore, these intrinsic job resources mediate the relationship between self-employment types and work engagement, highlighting their pivotal role. The findings emphasize that both direct and mediated effects contribute positively to work engagement among self-employed workers. This research offers practical insights into the role of intrinsic resources in enhancing engagement and provides theoretical contributions to self-employment literature. Further studies are suggested to explore the moderating influence of demographic and contextual factors in different self-employment settings.